Parmenides and the “First God”: Doxographical Strategies in Philodemus’ On Piety - Vassalo, Christian (Hyperboreus, 2016)
Among the several Herculanean testimonia to Parmenides, fr. 13 of PHerc. 1428 no doubt represents the most important piece of evidence for this pre-Socratic philosopher. A new autopsy of the papyrus made a reconstruction of the name ‘Eros’ at line 12 possible. Within the Doxa section of Parmenides’ poem, Eros is notoriously described as the ﬁrst of the gods to be created by Aphrodite (DK 28 B 13). In fr. 12 DK, Aphrodite is deﬁned in turn as the goddess governing the universe, who represents the balancing point of the astronomical theory of celestial spheres. In the second part of the Herculanean fragment, Philodemus  says that, according to Parmenides, the “ﬁrst god” would be inanimate and that gods who were generated by him would have, in the view of mortal people, the same passions of human beings. The paper argues that Philodemus could have (a) either intentionally mixed his sources in order to create a pendant between PHerc. 1428’s frs. 12 (on Xenophanes) and 13 (on Parmenides); (b) gone back to an older tradition, later developed by early Stoicism, which exactly describes the “ﬁrst god” as the ruler of the universe and absolutely devoid of human passions; (c) or mixed some attributes of Parmenides’ god with those ascribed to One by his follower Melissus.